IMPLEMENTASI GOOD CORPORATE GOVERNANCE PADA PT BANK SYARIAH INDONESIA TBK: STUDI KASUS DI KC PEMATANG SIANTAR PERINTIS - Faris Andrawika Harahap; Widya Anggraini; Imel Santika Siregar; Ahmad Wahyudi Zein (INTERNATIONAL, Journal of Sharia Business Management, 2025)
Good Corporate Governance (GCG) is a fundamental aspect of banking management in maintaining public trust and ensuring business sustainability, particularly in Islamic banking which operates under prudential and Sharia compliance principles. This study aims to analyze the implementation of Good Corporate Governance principles at PT Bank Syariah Indonesia Tbk, Pematangsiantar Perintis Branch Office. The research employs a qualitative approach using a case study method. Data were collected through semi-structured interviews with employees and supported by documentation analysis of the company’s governance policies and guidelines. The results indicate that the implementation of GCG at BSI Pematangsiantar Perintis Branch has been carried out effectively, as reflected in the application of transparency, accountability, responsibility, independence, and fairness in daily operations. Clear division of roles and responsibilities, internal control systems, and compliance with regulations and Sharia principles are the main factors supporting GCG implementation. However, challenges remain in maintaining consistent application across all operational units. Overall, the implementation of Good Corporate Governance plays an important role in supporting sound and sustainable Islamic banking governance.